2023
DOI: 10.1111/ijfs.16558
|View full text |Cite
|
Sign up to set email alerts
|

The Cyperus esculentus starch‐based bioactive films: characterisation, UV‐shielding and antioxidant capacity

Abstract: Summary This study aimed to develop a novel antioxidant film for food packaging based on Cyperus esculentus starch and thymol. The mechanical, physicochemical and antioxidant properties of composite films were investigated. The C. esculentus starch showed good film‐forming properties. Incorporating of thymol improved the elongation at break and ultraviolet barrier property of the films, meanwhile decreased the moisture content of the films. Scanning electron microscopy showed good compatibility between starch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In addition, TNS can be used as starch-based bioactive films and fillers on chitosan films. Li et al 18 developed bioactive films based on TNS incorporating thymol (0%, 1%, 2%, and 3%) by the solution casting method. The TNS showed good film-forming properties and good compatibility with thymol.…”
Section: Uses Of Tiger Nut Starchmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, TNS can be used as starch-based bioactive films and fillers on chitosan films. Li et al 18 developed bioactive films based on TNS incorporating thymol (0%, 1%, 2%, and 3%) by the solution casting method. The TNS showed good film-forming properties and good compatibility with thymol.…”
Section: Uses Of Tiger Nut Starchmentioning
confidence: 99%
“…Recent research has shown that TNS can be an ingredient for food and non-food applications. [16][17][18] However, a lack of systematic knowledge hinders the efficient utilization of TNS as a sustainable crop resource.…”
Section: Introductionmentioning
confidence: 99%